ABOUT THE RESULTS OF THE STUDY FOR SOME FACTORS WHICH INFLUENCE THE AWARENESS OF THE CITIZENS OF THE RUSSIAN FEDERATION ABOUT THEIR RIGHTS IN DRUG SUPPORT SYSTEM - T. V. Rejhtman (Фармация и фармакология (Пятигорск), 2015)
An openness and awareness formation of Russian population about their rights in drug support system (DSS) are considered to be of the main priorities of “Strategy for Drugs Support of the Population of the Russian Federation up till 2025”.